Work-Life Balance and Work Satisfaction in Workplace - Soo, Chin Hock (2014)
This study aims to investigate whether the workplace environment in an ICT organizations are conducive for the employees to use work-life balance and secondary investigation will involving whether the ability to have work-life balance will increase the happiness and this job satisfaction and leads to higher productivity. A questionnaire which consisted of all the work-life balance activities in the ICT organization were sent out and a total of 94 respondents whom worked in ICT organizations have responded. It was observed that in Malaysia ICT organizations, there is clear evidence that workplace environment are conducive of employees to have work-life balance as part of Corporate Social Responsibility policy and responses show that the management supports the employees to have work-life balance. The findings show despite having a workplace environment and management supportive of work-life balance programs in workplace, employees are still not happy with the organizations and thus actively looking for jobs outside the organizations. There may be more factors which should be accountable to the model framework used in the research such as salary and stress level which was not included.